Role playing and emotional competence in school-age children (a causality approach) - Gita Romadhoni Solikhah; Siti Suminarti Fasikhah; Sofa Amalia (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
School age is a time when the children begin to know more complex emotional expressions, so they need to learn about emotional competence to express and regulate them appropriately. One effective learning method to improve children’s emotional competence is role playing. The purpose of this study was to use the role playing method to improve the emotional competence of school-age children. This study used a quasi-experimental research design of two group pretest-posttest. This study used primary-school-age population and the target population of this study was the second grade of elementary-school children. This study involved 16 participants and was divided into an experimental group and a control group. This study used an instrument to measure emotional competence. The results show significant increase on the Wilcoxon test and it can be concluded that the role-playing method can be used to improve the emotional competence of school-age children.